Mechanisms of Music Impact: Autonomic Tone and the Physical Activity Roadmap to Advancing Understanding and Evidence-Based Policy - McCrary, J. Matt; Altenmüller, Eckart (Frontiers in Psychology, 2021)
Research demonstrates that both music-making and music listening have an ability to modulate autonomic nervous system activity. The majority of studies have highlighted acute autonomic changes occurring during or immediately following a single session of music engagement. Several studies also suggest that repeated music-making and listening may have longer-term effects on autonomic tone – the prevailing balance of sympathetic vs. parasympathetic activity. Autonomic imbalance is associated with a range of neurodegenerative and neurodevelopmental disorders, mental health conditions and non-communicable diseases. Established behavioral interventions capable of restoring healthy autonomic tone (e.g. physical activity; smoking cessation) have demonstrated remarkable efficacy in broadly promoting health and preventing disease and up to 7.2 million annual deaths. Accordingly, this article proposes that music’s suggested ability to modulate autonomic tone may be a key central mechanism underpinning the broad health benefits of music-making and listening reported in several recent reviews. Further, this article highlights how physical activity research provides a relevant roadmap to efficiently advancing understanding of music’s effects on both autonomic tone and health more broadly, as well as translating this understanding into evidence-based policy and prescriptions. In particular, adapting FITT – Frequency, Intensity, Timing, Type – criteria to evaluate and prescribe music-making and listening in observational and intervention studies has excellent prospective utility.